Harmonisasi Kewenangan Antara Kementerian Desa dan Kementerian dalam Negeri dalam Pembangunan Desa: Tinjauan Hukum - Menu, Moh Syamsurya; Ahmad, Mahmud; Moonti, Roy Marthen (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Village development is the main focus of Indonesia's national policy, especially after the enactment of Law Number 6 of 2014 concerning Villages. In its implementation, the role of the Ministry of Villages (Kemendesa) and the Ministry of Home Affairs (Kemendagri) is very important, however, disharmony of authority often occurs which hampers the effectiveness of these policies. This research aims to analyze the disharmonization of authority between the two ministries and formulate a harmonization solution from a legal perspective to increase more efficient and sustainable village development. The method used is a normative approach with comparative juridical analysis of existing regulations, which include related laws and policies. The research results show that there are overlapping regulations and roles between the Ministry of Villages and the Ministry of Home Affairs in aspects of preparing the RPJMDes, managing village funds, as well as coaching and supervising village heads. This research suggests the need for clear legal reconstruction and better coordinating mechanisms between the two ministries to avoid conflicts of authority that could hinder the achievement of village development goals. In conclusion, harmonization of authority normatively, institutionally and technically is very necessary to increase the effectiveness of village development and provide better legal certainty.